Hepatic Hilar Lymph Node Resection in Cytoreductive Surgery for Advanced Ovarian Cancer: A Necessity or Not? - Huang H; Wei R; Long Y; Mo Y; Xie Y; Yao D (Cancer Management and Research, 2021)
Honglian Huang,1,* Renjie Wei,1,* Ying Long,2 Yu Mo,1 Yu Xie,3 Desheng Yao2 1Hechi People’s Hospital, Hechi City, Guangxi Zhuang Autonomous Region, People’s Republic of China; 2Gynecologic Oncology Department, Guangxi Medical University Affiliated Cancer Hospital, Nanning City, Guangxi Zhuang Autonomous Region, People’s Republic of China; 3Obstetrics and Gynecology Hospital of Fudan University, Shanghai, People’s Republic of China*These authors contributed equally to this workCorrespondence: Desheng Yao; Yu Xie Tel/Fax +86-771-5330700; Tel +86-21-33189900Fax +86-21-63450900Email yaodesheng@gxmu.edu.cn; yuxie18@fudan.edu.cnObjective: This review aims to clarify the necessity of hepatic hilar lymph node resection on advanced ovarian cancer patients.Background: PARP inhibitors and surgery have significantly improved the survival of patients with ovarian cancer. However, for patients with advanced ovarian cancer, there are often extensive epigastric disseminated metastatic lesions, especially the lymph nodes in the hepatic hilar area. Because of the complicated anatomical relationship and lack of experience in this area, this is easily ignored by gynecological oncologists.Methods: Through the retrieval and analysis of the current database, namely PubMed, Medline, Web of Science, EMBASE, Cochrane Library, and Wangfang, etc., the literature regarding this topic published before March 2021 were thoroughly investigated.Conclusion: For the hepatic hilar regional lymph node surgery, through careful preoperative evaluation, surgical-indication clarification, appropriate case selection, standardized surgical operations and multidisciplinary cooperation with general surgeons, the prognosis of patients is significantly improved. Postoperative complications are also safe and controllable and convincing. To conclude, the application of hilar region lymph node cytoreductive surgery for patients with advanced ovarian cancer is a feasible and preferred choice.Keywords: advanced ovarian cancer, hilar lymph node, cytoreductive surgery